Nursing care for patients with spinal cord tumors in the Raudhah 5 room of DR. Zainoel Abidin General Hospital Banda Aceh - Dinda Putri Septya Liana; Laras Cyntia Kasih (PT WIM Solusi Prima, 2026)
Spinal medulla tumors tend to metastasize to the spine, so it is common for patients with these tumors to experience neurological problems such as paraplegia and muscle weakness. This final scientific paper aims to provide holistic nursing care using a nursing process approach for patients with spinal medulla tumors in Room Raudhah 5 at Dr. Zainoel Abidin General Hospital, Banda Aceh. The nursing process is divided into preoperative and postoperative stages. During the assessment phase, it was noted that the patient complained of lower back pain, inability to walk, and had not had a bowel movement for three days (preoperative), and later reported pain at the postoperative site with a pain scale of 7 on the NRS, along with a postoperative laminectomy wound, limited movement, and elevated leukocyte levels (postoperative). Nursing diagnoses included acute pain, disturbance of physical mobility, skin integrity issues, constipation, and risk of infection. Interventions involved deep breathing relaxation techniques, pain distraction through Quran recitation, finger hold technique, passive ROM exercises, a high-fiber diet, abdominal massage, and sterile wound care. In the evaluation stage, after four days of preoperative care and one day postoperative, it was found that issues such as acute pain, mobility disturbances, constipation, and skin integrity problems had been resolved. It is hoped that nurses can educate and train patients and families to independently perform interventions like pain management and passive ROM exercises at home, ensuring continuous care and supporting optimal recovery.